Towards sustainable halal bottled water: integrating circular economy and qualitypreneur for small-scale producers - Ali, Iqmi Qaisah; Fatimah, P. L. Rika (Journal of Halal Product and Research, 2025)
This paper explores the integration of circular economy principles and qualitypreneur within the halal bottled drinking water industry in Indonesia, proposing a conceptual framework to enhance sustainability and product quality. The increasing environmental challenges, particularly plastic waste and resource depletion, call for innovative approaches in waste management and production processes, by examining the intersection of the circular economy, which emphasizes waste reduction, reuse, and recycling, with qualitypreneur, which is focused on continuous product innovation and quality improvement. This study highlights how these two frameworks can jointly contribute to the production of eco-friendly and halal-compliant bottled water. Through a structured literature review and theory synthesis, this research develops a conceptual model for small-scale halal bottled water producers. The model emphasizes sustainable production practices, recyclable packaging, and robust quality management systems, while also addressing the sector's barriers and challenges, including high production costs, regulatory complexities, and limited infrastructure. The study concludes that integrating these two concepts not only aligns with the growing demand for sustainable products but also enhances the competitive advantage of halal bottled water businesses. This paper provides theoretical and practical insights for producers, policymakers, and researchers, aiming to foster a more sustainable and innovative halal bottled water industry   Keywords: Circular Economy, Halal Bottled Water, Qualitypreneur, Sustainability, Waste Management